On-site personal protective equipment signage and use by road construction workers in Ghana: a comparative study of foreign- and locally-owned companies - Isaac Kofi Yankson; Nana Kwame Nsiah-Achampong; Paul Okyere; Francis Afukaar; Easmon Otupiri; Peter Donkor; Charles Mock; Ellis Owusu-Dabo (BMC, 2021)
Abstract Background Road construction work has specific risks and safety issues which have not been adequately addressed in most low- and middle-income countries, especially Africa. The objective of this study was to determine the prevalence of personal protective equipment (PPE) use during road construction activities by workers in foreign- owned against locally-owned road construction companies in Ghana. Methods An institution-based cross-sectional survey was undertaken during January - March, 2020 to study 389 road construction workers who were actively working on site. They were unobtrusively observed to capture whether or not they wore the appropriate PPE at the time of the survey. The PPE of interest were: hard hat, goggles, shoes, nose masks, hearing protection, gloves and reflective vests/apparel. On-site posted PPE signage was also checked. Results Majority of workers were males (96.9%) and labourers (53.5%). Similar numbers of workers in locally-owned (195) and foreign-owned (194) companies were studied. Use of PPE varied considerably by type: shoes (78.7%), reflective vest (44.5%), gloves (30.6%), hard hat (27.0%), nose mask (17.2%), goggles (11.3%) and hearing protection (10.8%). For all types of PPE, use was higher for workers in foreign-owned companies compared with locally-owned companies: goggles (Odds ratio [OR] 55.2), hearing protection (OR 52.0), gloves (OR 23.7), hard hat (OR 20.2), nose mask (OR 17.8), reflective vest (OR 5.3) and shoes (OR 4.1), (p<0.001 for all ORs). No site had any signage to promote PPE use. Conclusions Majority of workers used shoes. Less than half of workers used other types of PPE and use of some types (goggles and hearing protection) was minimal. Workers in foreign-owned companies were significantly more likely to use all the seven types of PPE than locally-owned companies. Although there is still room for improvement in foreign-owned companies, locally-owned companies should be able to attain similar PPE use to that in foreign-owned companies. Necessary PPE should be provided and site supervisors should encourage workers to wear PPE when on site.